Normative Analysis of the Application of Balinese Customary Law in Determining Child Adoption - Hakim, Lukman; Rahmawati, Alfi; Akbar, Raihan Aulia; Tamam, Badrut (Riviera Publishing, 2025)
Adoption in Balinese customary law, known as